Patients with both Langerhans cell histiocytosis and Crohn's disease highlight a common role of interleukin‐23. (8th October 2020) - Kvedaraite, Egle; Lourda, Magda; Han, HongYa; Tesi, Bianca; Mitchell, Jenée; Ideström, Maja; Mouratidou, Natalia; Rassidakis, George; von Bahr Greenwood, Tatiana; Cohen‐Aubart, Fleur; Jädersten, Martin; Åkefeldt, Selma Olsson; et al.
Abstract: Aim: To present the first case series of patients with Langerhans cell histiocytosis (LCH) also affected by Crohn's disease (CD), both of which are granulomatous diseases, and in LCH investigate the role of interleukin (IL)‐23, which is a well‐described disease mediator in CD. Methods: A case series of three patients with LCH and CD were described; a cohort of LCH patients (n = 55) as well as controls (n = 55) were analysed for circulating IL‐23 levels; and the relation between the percentage of LCH cells in lesions and circulating IL‐23 levels was analysed in seven LCH patients. Results: Differential diagnostic challenges for these two granulomatous diseases were highlighted in the case series, and it took up to 3 years to diagnose CD. Elevated IL‐23 levels were found in LCH patients. The amount of lesional LCH cells correlated with the levels of circulating IL‐23. Conclusion: Both CD and LCH should be considered in patients with inflammatory gastrointestinal involvement. The IL‐23 pathway is a common immunological trait between these two granulomatous diseases.